Exopolysaccharides of lactic acid bacteria isolated from honeybee gut and effects of their antibiofilm activity against Streptococcus mutans - BASAR KARACA (Anais da Academia Brasileira de Ciências, 2023)
Abstract Streptococcus mutans is one of the main factors in formation of cariogenic biofilms. New strategies need to be developed to reduce the formation of cariogenic biofilms. For this purpose, bacterial exopolysaccharides (EPS) could be considered as new agents against biofilms. Therefore, cell-bound (b-EPS) and released exopolysaccharides (r-EPS) were extracted from the strains Apilactobacillus kunkeei K1.10 and Latilactobacillus curvatus Kar.9b isolated from the microbiota of honeybees, and their antibiofilm effects on S. mutans biofilm formation were determined. The highest reduction in biofilm formation was achieved by r-EPS of L. curvatus Kar.9b and A. kunkeei K1.10. Scanning electron micrographs (SEM) showed that r-EPS inhibited biofilm formation by reducing adhesion of S. mutans. To increase the production of r-EPS from A. kunkeei K1.10, the effects of different incubation conditions were also analyzed. The highest EPS production was obtained during 48 h-incubation at 37ºC in a medium containing 1% fructose. r-EPS can be used as a raw material to inhibit cariogenic biofilms. Further studies revealing the detailed structural analysis of r-EPS and the mechanism of action of its antibiofilm effect could be beneficial. Finally, b-EPS and r-EPS from lactic acid bacteria were found to have very different properties in terms of their antibiofilm properties.